2021
DOI: 10.1080/21655979.2021.1944455
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of carbohydrate sulfotransferase 12 decreases the proliferation and mobility of glioblastoma cells via the WNT/β-catenin pathway

Abstract: Glioblastoma (GBM) is a common malignant tumor of the brain. Members of the carbohydrate sulfotransferase (CHST) family are deregulated in various cancer types. However, limited data are available on the role of the members of the CHST family in the development of GBM. The present study aimed to identify the role of significant members of the CHST family in GBM and explore the effects and molecular mechanisms of these significant members on GBM cell proliferation and mobility. In the current study, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Wnt signaling pathway contributes to EMT when extracellular E-cadherin is degraded, β-catenin is able to translocate into the nucleus to induces EMT [ 30–32 ]. The deregulation of Wnt signaling is implicated in the progression of various cancers, such as papillary thyroid cancer [ 33 ], glioblastoma [ 34 ], breast cancer [ 35 ] and liver cancer [ 36 ]. In CRC, TGF-beta1 positively regulates B7-H4 through miR-155/miR-143 axis, thereby promoting cancer cells immune escape [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling pathway contributes to EMT when extracellular E-cadherin is degraded, β-catenin is able to translocate into the nucleus to induces EMT [ 30–32 ]. The deregulation of Wnt signaling is implicated in the progression of various cancers, such as papillary thyroid cancer [ 33 ], glioblastoma [ 34 ], breast cancer [ 35 ] and liver cancer [ 36 ]. In CRC, TGF-beta1 positively regulates B7-H4 through miR-155/miR-143 axis, thereby promoting cancer cells immune escape [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…showed that knocking down carbohydrate sulfotransferase 12 can reduce the proliferation and motility of glioblastoma cells through the WNT/βcatenin pathway (24). Tyrosine protein sulfotransferase (TPST) is mainly divided into two subtypes, TPST1 and TPST2 (25).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, SEMA3B-AS1 is downregulated in GBM and overexpression of SEMA3B-AS1 can downregulate cyclin D1 and suppress GBM cell proliferation possibly through miR-195. With the increased understanding of the molecular mechanism of GBM [ 26 , 27 ], lncRNAs are expected to be targeted to treat GBM.…”
Section: Discussionmentioning
confidence: 99%